2008
DOI: 10.2527/jas.2007-0762
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of young beef bulls alters circulating physiological parameters that may be effective biomarkers of stress1

Abstract: Transportation causes stress in cattle that may alter numerous physiological variables with a negative impact on production and health. The objectives of the current study were to investigate the physiological effects of truck transportation and to characterize a pattern of phenotypes in the circulation that may aid in the early identification of stress-susceptible animals that often succumb to severe respiratory disease. Thirty-six young beef bulls (Aberdeen Angus, n = 12; Friesian, n = 12; and Belgian Blue x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
82
5
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 33 publications
17
82
5
4
Order By: Relevance
“…The observed weight loss in this study is consistent with previous reports in the literature. However, the calves in our study showed an 8% loss in BW where as Arthington et al (2003) reported a 2 to 3% loss in BW after a 3-h transportation event and Buckham Sporer et al (2008) reported shrinkage of 10% in calves (approximately 230 kg) transported for over 9 h. This supports the hypothesis that percentage of weight loss during transportation is likely associated with the duration of the transportation event as was previously suggested (Cernicchiaro et al, 2012).…”
Section: Body Weightsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed weight loss in this study is consistent with previous reports in the literature. However, the calves in our study showed an 8% loss in BW where as Arthington et al (2003) reported a 2 to 3% loss in BW after a 3-h transportation event and Buckham Sporer et al (2008) reported shrinkage of 10% in calves (approximately 230 kg) transported for over 9 h. This supports the hypothesis that percentage of weight loss during transportation is likely associated with the duration of the transportation event as was previously suggested (Cernicchiaro et al, 2012).…”
Section: Body Weightsupporting
confidence: 87%
“…A 133% increase in fibrinogen was reported in a study with 32 calves that were transported for 3 h (Arthington et al, 2003). Conversely, a 28% reduction in fibrinogen over 48 h after transportation was reported in a study involving 36 calves transported for 9 h (Buckham-Sporer et al, 2008). Therefore the usefulness of fibrinogen as a biomarker of inflammation after transportation requires further investigation.…”
Section: Fibrinogenmentioning
confidence: 95%
“…It is likely that because the cortisol response was only short-term there was not a decrease in b-hydroxyl-butyrate. Changes in b-hydroxyl-butyrate are usually associated with longer-term nutritional stressors in cattle (Shaw and Tume 1992); however, a previous study with bulls found no effect of transportation stress on b-hydroxyl-butyrate, although there was an acute increase in plasma cortisol (Buckham Sporer et al 2008).…”
Section: Discussionmentioning
confidence: 86%
“…Earley and O'Riordan [9] had found an unchanged concentration of haptoglobin following transportation, while the plasma fibrinogen concentrations were significantly reduced. Buckham Sporer et al [5] observed a reduction of haptoglobin and fibrinogen posttransportation. No effect of slaughterhouse on APPs has been reported.…”
mentioning
confidence: 97%